Geochemical and magnetic data on anthropogenic ashes from municipal solid waste incineration (MSWI) - Funari, Valerio (Data Brief, 2020)
This paper reports supplementary information to “Understanding room-temperature magnetic properties of anthropogenic ashes from municipal solid waste incineration to assess potential impacts and resources” [1]. The sample-set is composed of 47 samples of bottom (BA) and fly (FA) ashes from Municipal Solid Waste Incineration (MSWI), including eight magnetic extracts of selected BA and FA materials. The sampling relies on a simple random sampling strategy at four different MSWI sites in Northern Italy [2]. X-Ray Fluorescence (XRF) analysis on pressed powder pellets, microscopic observations on thin sections and stubs, and magnetic analysis were carried out. Various magnetic measurements are presented: the magnetic susceptibility measured at two different frequencies (0.47 and 4.7 kHz); the mass-specific susceptibility of ARM (χ(ARM)), expressed in m(3)/kg, calculated after mass-normalization and bias DC field correction; experiments for isothermal remanent magnetization (IRM) experimented were also conducted. The latter measurement allowed the calculation of additional parameters, such as the coercivity of remanence (B(0cr)) and the S-ratio [3]. The IRM acquired in a field of 1.0 T was regarded as the saturation IRM (SIRM). Mass-specific magnetic susceptibility (χ) was calculated by dividing the volume susceptibility by the sample mass. Finally, hysteresis loops and backfield curves at room temperature were measured on selected samples and are available. Data can be reused as groundwork information in future studies on MSWI residues. It would be essential to produce new data on geochemical and magnetic characteristics of MSWI residues to assure good coverage of data for enhanced sustainability of these heterogeneous streams of anthropogenic materials. This combination of methods will contribute to paving the way for quick and reliable resource assessment as well as to promote environmental sustainability.